AN EXPERIMENTAL SETUP FOR THE ANALYSIS OF ANALOGUE DEFORMATION EXPERIMENTS USING THE ROTATING POLARISER STAGE - Fueten F.; Hynes K.; Van Luttikhuisen R.L. (My University, 2002)
A new experimental setup for the analysis of deformation of rock analogues is presented. The hardware component consists of a rotating polariser stage and the software component includes several specialised pieces of software. During experiments the software is able to construct data sets in the form of specialised images that contain information on grain shape and crystallographic orientations. Several different types of movies with frames spaced as close as 2min apart can be created during the experiment, which convey crystallographic and shape information in a semi-continuous form. This setup can be adapted to a variety of optical deformation rigs.
Keywords: ROTATING POLARISER STAGE; ANALOGUE MODELLING; C-AXIS MEASUREMENTS; DEFORMATION MOVIES; FABRIC ANALYSIS